Development of the traction system structure of a shunting diesel locomotive with a hybrid power supply scheme (Transport systems and technologies, 2024)
In this work, the structure of the traction system of a shunting diesel locomotive with hybrid power, which performs both shunting work at the station and hauling work, is proposed. In order to develop the structure of the traction system, which will work effectively in both modes of operation of the shunting diesel locomotive, an analysis of the structures of the traction systems of diesel locomotives with hybrid power, produced by the world's leading companies, is carried out. In order to choose the optimal type of storage device, an analysis of the advantages and disadvantages of supercapacitor batteries and lithium-ion batteries is carried out. On the basis of the analysis of the structures of traction systems of diesel locomotives with hybrid power of leading companies and the advantages and disadvantages of supercapacitor batteries and lithium-ion batteries, the structure of the traction system of a shunting diesel locomotive with hybrid power, which performs both shunting work at the station and hauling work, is developed. In the proposed traction system structure, each traction motor receives power from a separate traction converter. The power for powering the traction motors during shunting work is transmitted from supercapacitor batteries, when carrying out hauling work - from lithium-ion batteries. This study can be used in the design of the traction system of a new and in the modernization of an existing shunting diesel locomotive.
Keywords: hybrid power supply; supercapacitor; lithium-ion battery; shunting diesel locomotive; traction system